Optimization tools for logistics - Reveillac, Jean-Michel (ISTE Press, Ltd ; Elsevier, 2015)
Optimization Tools for Logistics covers the theory and practice of the main principles of operational research and the ways it can be applied to logistics and decision support with regards to common software. The book is supported by worked problems and examples from industrial case studies, providing a comprehensive tool for readers from a variety of industries.